1985
DOI: 10.1017/s0021859600043148
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of upland rice with blackgram [Vigna mungo (L.)]

Abstract: To increase the productivity of fields growing direct-seeded upland rice, which usually gives low yields because of weed competition, unsatisfactory establishment and exposure to intermittent drought, an experiment on intercropping of rice with blackgram was conducted in two seasons under rainfed conditions on a sandy loam soil. Blackgram, when intersown simultaneously in one row in every 30 om wide space left between the stand of 10 cm apart paired rows of rice, reduced the yield of rice by 1-64 t/ha. When on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…Number of seeds/pod: Deferred sown blackgram recorded significantly higher number of seeds per pod over simultaneously sown crop which was found to be statistically at par with sole crop (Table 3). This result supported the finding of SENGUPTA et al (1985).…”
Section: Blackgramsupporting
confidence: 92%
See 1 more Smart Citation
“…Number of seeds/pod: Deferred sown blackgram recorded significantly higher number of seeds per pod over simultaneously sown crop which was found to be statistically at par with sole crop (Table 3). This result supported the finding of SENGUPTA et al (1985).…”
Section: Blackgramsupporting
confidence: 92%
“…The effect of legumes on increasing the number of filled grains/panicle might be due to the effect of complementarity. This result cor-roborated the findings of SENGUPTA et al (1985).…”
Section: Ricesupporting
confidence: 89%
“…In India, Sengupta et al (1985) demonstrated intercropping blackgram (Vigna mungo [L.] Hepper) into rice (21 d after planting rice) effectively suppressed weed growth, eliminated one hand weeding, and increased total crop yield and income, as compared to sole-cropped rice. Ali (1988), also working in India, reported that total seed yields of pigeonpea/mungbean (Vigna radiata [L.] R. Wilczek) intercrops without any hand weeding were very close to yield levels obtained from weeded, sole-cropped pigeonpea.…”
Section: Weed Suppression By Intercropsmentioning
confidence: 99%
“…must be grown separately from sawa millet (Echinochloa colona), as the millet is highly competitive and extremely aggressive towards rice (Galinato et al 1999). Vigna mungo is not a successful intercrop with rice as it reduces yields (Sengupta et al 1985), though it can be row intercropped with Sesamum sp., which can also be intercropped with millet, as they all have similar water, fertility, soil, salinity and pH requirements. Sesamum sp.…”
Section: Differentiating Indus Cropping Strategiesmentioning
confidence: 99%